2009
DOI: 10.21608/jfds.2009.115327
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes of Some Breads Made From Wheat Flour Substituted by Different Levels of Whole Amaranth Meal

Abstract: Amaranth plant grows rapidly, with a high tolerance to arid conditions and poor soils. So, a trial was made to use amaranth meal in producing popular Egyptian breads. The quality attributes of balady, shamy (Egyptian traditional breads) and pan bread produced from wheat flour alone or substituted by different levels of whole amaranth meal were studied. The quality of the produced breads from different blends was compared to that of bread produced from wheat flour as control. Chemical composition, mineral conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
2
6
0
1
Order By: Relevance
“…The dried green curd of pea peel (DGCPp) had significantly higher contents of protein, ether extract, and ash on a dry weight basis than the wheat flour (Table 1 ). These results agreed with other studies 20 , 22 – 24 who also found higher protein and mineral contents in the extracted juice from pea peel. DGCPp protein content (35.00 ± 2.28%) was higher than those of the pea pod powder (PPP, 11.99 ± 0.31%) 20 , which can be attributed to the new effective method used for DGCPp preparation in which insoluble dietary fiber and brown juice were eliminated to obtain a moist green curd with higher protein content.…”
Section: Resultssupporting
confidence: 93%
“…The dried green curd of pea peel (DGCPp) had significantly higher contents of protein, ether extract, and ash on a dry weight basis than the wheat flour (Table 1 ). These results agreed with other studies 20 , 22 – 24 who also found higher protein and mineral contents in the extracted juice from pea peel. DGCPp protein content (35.00 ± 2.28%) was higher than those of the pea pod powder (PPP, 11.99 ± 0.31%) 20 , which can be attributed to the new effective method used for DGCPp preparation in which insoluble dietary fiber and brown juice were eliminated to obtain a moist green curd with higher protein content.…”
Section: Resultssupporting
confidence: 93%
“…However, the size of the losses was determined not only by the proportion, but also by the form of the additives used. Similar results were obtained by Bilek and Turhan [ 23 ], simultaneously showing the reduction of cooking losses with the addition of linseed flour to beef cutlets, and Longato et al [ 21 ] in poultry burgers with amaranth seeds and Sharoba [ 40 ] in sausages with amaranth flour.…”
Section: Resultssupporting
confidence: 86%
“…The volume of baked product and volume of bread loaf decreased significantly at higher concentration of amaranth flour, as the supplementation of wheat flour with nonglutinous flour reduces the gluten content and thus lowers the bread volume [ 28 ]. On the other hand, Sanz-Panella et al [ 20 ] described this phenomenon as there is a high amount of water that results in gluten dilution, physical interactions, and chemical reactions among fibre components, and thus, during mixing, fermentation, and baking steps, the gluten matrix formation is affected.…”
Section: Resultsmentioning
confidence: 99%